Long-term efficacy of endovascular vs open surgical repair for complicated type-B aortic dissection: a single-center retrospective study and meta-analysis - Zhu,Y. (2016)
This study aimed to evaluate the long-term survival and risk factors of traditional open surgical repair (OSR) vs thoracic endovascular aneurysm repair (TEVAR) for complicated type-B aortic dissection (TBAD). A total of 118 inpatients (45 OSR vs 73 TEVAR) with TBAD were enrolled from January 2004 to January 2015. Kaplan-Meier curves and Cox proportional hazards analysis were performed to identify the long-term survival rate and independent predictors of survival, respectively. Meta-analysis was used to further explore the long-term efficacy of OSR and TEVAR in the eight included studies using Review Manager 5.2 software. An overall 10-year survival rate of 41.9% was found, and it was similar in the two groups (56.7% OSR vs 26.1% TEVAR; log-rank P=0.953). The risk factors of long-term survival were refractory hypertension (OR=11.1; 95%CI=1.428-86.372; P=0.021] and preoperative aortic diameter >55 mm (OR=4.5; 95%CI=1.842-11.346; P=0.001). Long-term survival rate did not differ significantly between OSR and TEVAR (hazard ratio=0.87; 95%CI=0.52-1.47; P=0.61). Compared with OSR, TEVAR did not show long-term advantages for patients with TBAD. Refractory hypertension and total aortic diameter >55 mm can be used to predict the long-term survival of TBAD in the Chinese Han population.